Education of Yesterday and Today. Reflections for teaching staff - Rodríguez Gómez, Juana María (Pulso. Revista de educación, 2007)
Between the past and the present of education there exists a great amount of objectives and intentions which mark the educational lines for the future. In this work, we acknowledge the achievements of the past as an illustrative base upon which we could initiate the path towards equality of opportunities, social transformation and the democratisation of the educative institutions: The schools seen as communities of learning and social change. In this process, the teachers play a very important role in the fl exibility of the academic structures as well as in the acknowledgement of the cultural, social and personal diversity of the students.